Objective reference points for compensation of teachers - V Smirnov; V Sadkov; T. . Lukyanchikova (Высшее образование в России)
The authors give an assessment of remuneration of higher school teachers and other socially significant professions. The new approach for remuneration of labor of these categories of theworkers is offered providing reproduction and accumulation of the human capital.